Dendrimeric peptide – montmorillonite intercalation compound - Kędzierski, M.; Janiszewska, J.; Moszumańska, I. (Polimery, 2021)
The solution intercalation method was used for immobilization of low-molecular-mass lysine–based peptide dendrimers (Lys-D, hydrochloride form) on montmorillonite (MMT). The intercalation was confirmed by X-ray diffraction and elemental analysis of the products. Analysis of Brunauer-Emmett-Teller (BET) nitrogen adsorption–desorption isotherms indicates that both interlayer and external clay surfaces are involved in the binding of dendrimeric peptides. Depending on the structure of Lys-D, including the location of protonated amino groups in peptide branches, the intercalation involves ion exchange between sodium montmorillonite and peptide ionic groups or proceeds leaving the intact peptide counterions. Thermogravimetric analysis (TGA) studies of MMT-Lys-D compounds indicate that the major mass-loss associated with the decomposition of peptide component is shifted to higher temperatures compared to the peptide itself.